Choosing between the Conventional Plates, Locking Plates, or Iliosacral Screws for Sacroiliac Joint Dislocation: A Biomechanical Comparison Study - Trixie Brevi Putri; Erwin Ramawan; Mohammad Zaim Chilmi; Kukuh Dwiputra Hernugrahanto; Jifaldi AMD Sedar; Fundhy S I Prihatanto (The Hip and Knee Journal, 2021)
Background: This study examines the comparison of biomechanical strengths of three kinds of the most familiar implants available in Indonesia: conventional and locking sacroiliac plates and screws, also iliosacral screws. Despite the common thought that iliosacral screws are preferred compared to conventional plates and screws due to its biomechanic superiority, this study tested whether the locking plates and screws could offer an alternative.Materials and Methods: This study was an in vitro experimental study with a Randomized Post Test - Only Control Group Design using pelvic bones from male cadavers aged 20-50 y.o. Twelve samples were divided into three treatment groups and one control group. Group P1 was fixed with two conventional plates, P2 was fixed with two locking plates, P3 was fixed with two iliosacral screws, and control group K with sacroiliac joint was intact. Each group was given an increasing load until a vertical shift of the sacroiliac joint ≥ 2.0 mm was obtained.Results: The average force load for 2 mm displacement among the fixation systems being tested shows a statistically significant difference (p0.05). Load failure force for 2 mm displacement in the locking plate and screw group has the highest average (591.33 ± 56.08 N) compared to the iliosacral screw group (583.67 ± 73.56 N) and conventional plate and screw group (574 ± 106.05 N).Conclusions: Biomechanically, the fixation system using two locking anterior sacroiliac plates and screws is more stable than the iliosacral screws and conventional sacroiliac plates and screws.